THE ANALYSIS OF SERVICES MARKETING MIX ON STUDENTS' DECISIONS IN CHOOSING UNIVERSITAS MUHAMMADIYAH SIDOARJO - Febriansah, Rizky (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2024)
In a highly competitive market, companies and service providers, especially those in higher education, may experience frequent shifts in consumer preference. The marketing mix strategy of the 7Ps, which consists of promotion, product, place, price, people, process, and physical evidence, can have a significant impact on a student's decision to choose a university. This study used a descriptive quantitative research method, utilizing a Likert scale survey distributed to 89 respondents. The survey measured variables such as promotion, product, location, price, people, process, and physical evidence. Multiple regression analysis was conducted, and the F-test and t-test were used with a 90% confidence level and a value of ὰ = 0.05. The regression coefficient of determination revealed that the independent variables explained 68.7% of the dependent variable (student decision). The variable of people had the highest value of 0.689 on the standardized coefficient, making it the most influential among the independent variables. The study concluded that the 7P marketing mix variables, particularly promotion, product, location, people, and physical evidence, positively and significantly impact a student's decision to choose Universitas Muhammadiyah Sidoarjo.